efektivitas Efektivitas Metode Peer Teaching berbantuan Software Statistika dengan Mengontrol Kemampuan Numerik pada Mahasiswa Teknik Informatika - I Made Dedy Setiawan (PendIPA Journal of Science Education, 2023)
Statistics learning in the classroom does not yet utilize relevant and effective technology to carry out various kinds of statistical computing. Apart from that, learning still prioritizes lecture methods and assignments in the form of practice questions at the end of learning, so this has an impact on statistics learning outcomes. The aim of this research is to determine the effectiveness of applying the peer teaching method assisted by statistical software by controlling the numerical abilities of INSTIKI students. The sampling technique uses purposive random sampling with a factorial design. Data was collected using numerical ability test instruments and learning outcomes tests. Data were analyzed descriptively, prerequisite testing, and hypothesis testing. The research results concluded that there were differences in learning outcomes through the application of peer teaching methods assisted by statistical software after controlling for numerical abilities. From Anakova's test results, it is known that numerical ability contributes 67.7% to statistics learning outcomes.